Patterns and trajectories of inequality in physical activity from childhood to adolescence in Kazakhstan - Ng, Kwok (Elsevier, 2025)
Objective: Sociodemographic differences in physical activity (PA) levels during the transition from childhood to adolescence, particularly in Central Asian countries, is lacking. In this study, we examine individual, family and environmental sociodemographic variables associated with PA among children and young adolescents in Kazakhstan.
Study design: Secondary data analyses of two nationally representative cross-sectional studies administered by parents of children (aged 7–9 y) and by self-report surveys (adolescents aged, 11–15 y).
Methods: The 2020 Childhood Obesity Surveillance Initiative (COSI) and 2018 Health Behaviour in School-aged Children (HSBC) studies were used. Predictors of daily PA by individual (gender, grade, weight status), family (family composition, family employment, family wealth), and environment (school location) factors were analysed through binary logistic regressions after adjusting for screen time.
Results: Among both children and adolescents, males were more physically active than females. Daily PA among children was positively associated with high family employment (OR = 1.23, CI = 1.03–1.48) or living in an urban location (OR = 0.58, CI = 0.49–0.70). Daily PA was associated with low family wealth, two-parent families (OR = 1.25 CI = 1.08–1.44) or living in a rural location (OR = 1.18 CI = 1.04–1.34) among adolescents.
Conclusion: In Kazakhstan, the trajectory of children’s and adolescent’s PA levels, differed according to individual, family and environmental characteristics , suggesting a need for age-specific, targeted interventions to promote PA, appropriate policies that promote programs in schools, communities, and development of infrastructure for physically active lifestyles.